2019
DOI: 10.1111/exd.14065
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of CCR5 in melanoma: An alternative immune checkpoint modulator

Abstract: Melanoma is a deadly tumor, which in recent years has been successfully treated with immune checkpoint inhibitors as PD-1/PD-L1 and CTLA-4 inhibitors and targeted therapy as BRAF and MEK inhibitors. However, immunotherapy poses deleterious side effects and pursuit of new therapeutic targets is warranted. As knowledge of tumor immunology advances, such targets are being recognized.C-motif chemokine receptor-5 (CCR5) is a receptor found on immune cells whose effects impact the immune response both to induce infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Targeted therapy interferes with mutation of the BRAF gene, which stimulates cells to develop abnormally and divide out of control, but the mutation occurs in around half of all melanoma [19]. In the case of immunotherapy, inflammatory response can be caused in any of the organs of the body [20]. Therefore, the development of new drugs for melanoma is urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted therapy interferes with mutation of the BRAF gene, which stimulates cells to develop abnormally and divide out of control, but the mutation occurs in around half of all melanoma [19]. In the case of immunotherapy, inflammatory response can be caused in any of the organs of the body [20]. Therefore, the development of new drugs for melanoma is urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis is that CCR5 ligands are involved not only in MDSC recruitment but also in their immunosuppressive polarization [136,137]. Therefore, given that melanoma is highly immunogenic and also immune evasive, inhibiting the CCL5/CCR5 axis with maraviroc was recently proposed as the next step in melanoma immunotherapy [176].…”
Section: Melanomamentioning
confidence: 99%
“… 142 The expression of CCR5 stimulates calcium signaling and thus elevates regulatory T cell differentiation and migration to inflammation sites and recent studies suggested that there has profound coaction between CCR5 and immune checkpoints function. 143 , 144 …”
Section: Regulation Of Immune Cells and Immune Checkpoints By Calcium...mentioning
confidence: 99%